INFLUENCE OF THE COMBINED ANTIHYPERTENSIVE THERAPY ON METABOLIC PROFILE AND CEREBRAL BLOOD FLOW IN PATIENTS WITH METABOLIC SYNDROME - E. M. Idrisova; T. P. Kalashnikova; I. Yu. Efimova (Рациональная фармакотерапия в кардиологии)
Aim. To study influence of the combined antihypertensive therapy on blood pressure (BP), glucose and lipid metabolism as well as cerebral blood flow in patients with metabolic syndrome (МS)Material and methods. 60 patients with MS aged of 35-65 y.o. were included in the study. 29 patients of the 1st group received verapamil SR (240 mg once daily) and indapamide retard (1,5 mg once daily). 31 patients of the 2nd group received verapamil SR (240 mg once daily) and enalapril (12,2±5,9 mg BID). Ambulatory BP monitoring, lipid profile, insulin and C-peptide levels, standard glucose tolerance test were performed. The single-photon emission computer brain tomography was performed in 11 patients of each group.Results. Combination of verapamil SR and enalapril showed more significant antihypertensive effect, improved carbohydrate metabolism and cerebral blood flow. However it worsened 24-hour BP profile. Combination of verapamil SR and indapamide retard increased fasting glycemia level within normal range, led to insignificant improvement of cerebral blood flow and did not worsen circadian BP rhythm. Both drug combinations improved lipid profile.Conclusion. Both drug combinations can be prescribed to MS patients. However diuretic based therapy demands regular control of glycemia level.